Słowo Boże – słowo wiary – słowo przepowiadania. Dogmatyka w relacji do egzegezy i homiletyki - Podhorecki, Norbert (Studia Pastoralne, 2026)
Presentation of the issue: In this study the author takes the view, that the role of dogmatic theology is to be a kind of link between the revealed and absorbed in faith the word of God (exegesis), and its proclamation, taking into account the diverse cultural, social or anthropological conditions (homiletics). Background: The Bible as the word of God and the first and most perfect testimony of His Revelation is and will remain the highest instance in the community of Church (norma normans non normata). Results: Every dogma expresses only a particular, defined part of the whole of the Christian faith and can be fully understood only by looking at the entirely Christian and biblical kerygma, at the other truths of the Deposit of Faith and by getting the right proportions between them (the hierarchy of truths). Conclusions: The task of every homilist and preacher is continuous exploration of revealed truths, which are expressed in the dogmatic formulae of the Church, in connection with a critical reflection on the workshop and the ways to communicate these contents to the people of God.